Produção do gênero resenha no oitavo ano do ensino fundamental: uma experiência mediada pelo procedimento da sequência didática - Costa, Dyuana Maria Soares da (2021)
Portuguese language teaching, specifically in most Brazilian schools, is still supported by theoretical-methodological options that prioritize a traditional approach, in which writing happens artificially and there is a lack of interaction marks; thus, the conditions of production and reception for the teaching-learning of writing are not taken into account. The teacher who works in this way does not prepare students to be competent textual producers, and does not enable them to write appropriately to the different socio-communicative situations in which they are inserted, inside or outside the school context, as proposed by the sociointeractionist conception of writing. Based on this assumption, we prioritize teaching procedural-discursive writing, through the execution of the didactic sequence, based on the principle that the sequenced activities can contribute for students to learn that discursive / textual genres have their functions, and thus, can be prepared to act efficiently and effectively through language, whether in reading and / or in the production of texts. In this perspective, our intervention has the general objective to analyze the students` perfomance in the textual production process of the genre review, with a view to the elaboration of a Pedagogical Notebook with the Didactic Sequence procedure of that genre. The research is of a qualitative, applied, descriptive, purposeful nature and with an interventional purpose, which configures it as action research. We take as a theoretical basis, regarding the theory of discursive genres, the views of Bakhtin (1986, 2000), Koch (2012) and Marcuschi (2008, 2010); on the didactic sequences, we are based on the studies of Dolz and Noverraz & Schneuwly (2004), and on the genre review we are based on Machado, Lousada and Abreu-Tardelli (2004), and Bronckart (2007). The analysis carried out was based on the textual productions, in their initial version, of the researched subjects. Thus, the corpus was composed of 10 (ten) reviews produced by students from a class of the 8th year of Elementary School Anos Finals, from a school in the municipal public network, in which we work as a teacher. Based on the initial production, we mapped the main problems presented by the students with regard to gender, and, based on this observation, a Pedagogical Notebook was prepared, which provides suggestions on how to work the modules, in order to remedy the difficulties presented. In this sense the didactic proposal evidenced in the Pedagogical Notebook fulfills the purpose of developing students` linguistic and discursive skills.